Islam and the Malay-Indonesian World Transmission and Responses - Riddell, Peter G. (University of Hawaii Press, 2001)
This study looks at the history of Islamic religious thought in the Malay-Indonesian world from the 13th to the 20th century bringing together the resuts of scholarship published over the last 100 years. It also addresses theological issues relevant to the wider Islamic world.